Developing the food industries through focus on intangible capital - Cleland, Andrew (New Zealand Science Review, 2010)
​New Zealanders seem to have a belief that we were always a rich country. This is not the case. We were very poor until the 1860s. The first exports, predominantly gold, brought about change, and then with the advent of refrigeration in 1882 we started to become well-off. However, only briefly were we truly world-leading.